Pengaruh Prosedur Kerja, Kompetensi, dan Kepuasan Kerja terhadap Produktivitas Kerja Karyawan PG. Asembagoes - Mohammad Yahya Arief; Maghfirotun Nisak (J-MAS (Jurnal Manajemen dan Sains), 2022)
The main purpose of this study was to determine the effect of work procedures, competencies, and job satisfaction on the productivity of employees Asembagoes sugar factory. The approach used is descriptive quantitative by looking at the relationship between variables and causal relationships. The research population is employees Asembagoes sugar factory and for sampling used saturated sampling technique, where all members of the population were sampled, namely 40 respondents. Data were collected through tests and questionnaires which were then tested using multiple linear regression analysis techniques. The results showed that the work procedure and competence variables had no partial effect on employee productivity. Only the job satisfaction variable has a significant effect on employee productivity. The variables of work procedures, competence, and job satisfaction have a simultaneous and significant effect on employee productivity. The value of the coefficient of determination or R square is 0.720, from these results all independent variables have a contribution of 72% to the dependent variable with a high level of accuracy, and the remaining 28% is influenced by other variables not included in the study.